Celebrating a face-to-face congress of young researchers in Optics after the pandemic years: the I NW MYRO - Carnero Bastián; de las Heras Alba; Doval Alejandro; Martín-Rodríguez Álex; Muñoz-Ramos Alicia; García-Cabrera Ana; Rodríguez-Fernández Carlos Damián; Insua-Costa Damián; Romo-Díez Irene; Rodríguez-Pérez Isabel; Prada-Rodrigo Javier; Varela-Carballo Javier; et al. (EPJ Web of Conferences, 2022)
This contribution reports the organization and celebration after the Covid-19 pandemic of a singular scientific conference focused on early-career researchers from the Spanish universities of Santiago de Compostela and Salamanca: the “I Northwest Meeting of Young Researchers in Optics (I NW MYRO)”.